Sustainable governance indicators 2020 Turkey report - GENÇKAYA, ÖMER FARUK (Bertelsmann Stiftung, 2020)
Following general elections originally scheduled for November 2019 but held in June 2018, President Recep Tayyip Erdoğan issued in July 2018 a presidential decree that abolished the office of the prime minister and introduced the mechanics of the country’s new presidential system. The new system undermines parliament’s legislative and oversight functions, weakens elected local administrations by placing administrative or financial restrictions on them yet lacks coordination, adaptation and sustainability in governance. The lack of judicial independence and qualified judicial staffing, combined with the lengthy prosecution procedures and trial periods within this system, have weakened the rule of law in Turkey. The Turkish government currently features 16 line ministries and nine policy councils, the latter of which are responsible for developing the government’s long-term strategy and reporting on progress made by the government. In addition, the growth of popular authoritarianism has further undermined legal certainty and the rule of law, exacerbated widespread social discrimination, and reinforced the presidential system and efforts to bypass the legislature in government processes. The war in Syria has had a profound impact on Turkish politics and society. The government’s extensive military counterinsurgency and border security operations in northern Syria as well as its dismissal of elected HDP mayors and appointment of so-called trustee mayors in the southeast provinces have exacerbated tensions with the Turkey-based Kurdistan Workers’ Party (PKK) and its Syrian extension, the Democratic Union Party (PYD) and the People’s Protection Units (YPG). The government appears to lack a clear strategy for ending the conflict in the country’s southeast region. Moreover, Turkey is host to more than 4 million Syrian nationals with Temporary Protected Status, whose social and economic integration remains unresolved. The uncertainty faced by these individuals poses challenges to Turkey’s political, social and economic future. Throughout the review period, the government continued to quash dissent by, for example, issuing open threats against perceived opponents such as activists, academics and journalists. Gender-based violence, hate speech, and the exclusion of specific groups such as Roma or LGBT individuals are ongoing significant problems that need to be addressed Civil society organizations continue to have only limited influence in decisionmaking processes. The massive polarization between pro- and antigovernment camps is present across all spheres of political, economic and social life. In the run-up to the June 2018 general elections, both the AKP, as well as its chair and the country’s president, Recep Tayyip Erdoğan, secured a parliamentary majority by forming an informal alliance with the Nationalist Movement Party (MHP), which broke up in the second half of 2018. However, the outcome of the 2019 Istanbul election rerun, which brought victory to the mayoral candidate who emphasized overcoming divisions, points to a brighter future. In part as a result of these electoral results, opposition parties in Turkey have won ground by forming an electoral alliance. Over the last decade, income and living standards have improved markedly in Turkey. However, Turkey was shaken by a currency crisis in 2018 that saw the Turkish lira fall substantially against the U.S. dollar and the euro. Though the government did introduce a few effective countermeasures in an effort to restore the lira, the government has nonetheless refused to invite the International Monetary Fund for help in solving the problem and has refused to introduce substantial structural reforms needed in government or in terms of macro- and microeconomic policies. Furthermore, environmental sustainability and efforts to achieve a high-tech, science-based society are not assured in Turkey. Increased government spending during the review period on areas such as research and development, education and vocational training, social policy, and healthcare mark a step forward, but the policies introduced thus far have yet to yield any sustainable results. On a more positive note, gains have been made in terms of security and safe living